Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve the system of equations using the method of substitution. Here are the equations:
[tex]\[ \begin{cases} -2 x + y = -5 \\ -4 y = 22 - 8 x \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
We start by solving the first equation for [tex]\( y \)[/tex]:
[tex]\[ -2 x + y = -5 \implies y = 2x - 5 \][/tex]
### Step 2: Substitute the expression for [tex]\( y \)[/tex] into the second equation
Next, we substitute [tex]\( y = 2x - 5 \)[/tex] into the second equation:
[tex]\[ -4 (2x - 5) = 22 - 8x \][/tex]
### Step 3: Simplify the substituted equation and solve for [tex]\( x \)[/tex]
First, expand and simplify the equation:
[tex]\[ -4 (2x - 5) = 22 - 8x \\ -8x + 20 = 22 - 8x \][/tex]
Notice that the terms [tex]\(-8x\)[/tex] on both sides cancel each other out:
[tex]\[ 20 = 22 \][/tex]
This is a contradiction because 20 does not equal 22. Therefore, the system of equations has no solution.
### Conclusion:
Since we have derived a contradiction, it indicates that the system of equations is inconsistent and there are no solutions.
[tex]\[ \text{No solutions} \][/tex]
[tex]\[ \begin{cases} -2 x + y = -5 \\ -4 y = 22 - 8 x \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
We start by solving the first equation for [tex]\( y \)[/tex]:
[tex]\[ -2 x + y = -5 \implies y = 2x - 5 \][/tex]
### Step 2: Substitute the expression for [tex]\( y \)[/tex] into the second equation
Next, we substitute [tex]\( y = 2x - 5 \)[/tex] into the second equation:
[tex]\[ -4 (2x - 5) = 22 - 8x \][/tex]
### Step 3: Simplify the substituted equation and solve for [tex]\( x \)[/tex]
First, expand and simplify the equation:
[tex]\[ -4 (2x - 5) = 22 - 8x \\ -8x + 20 = 22 - 8x \][/tex]
Notice that the terms [tex]\(-8x\)[/tex] on both sides cancel each other out:
[tex]\[ 20 = 22 \][/tex]
This is a contradiction because 20 does not equal 22. Therefore, the system of equations has no solution.
### Conclusion:
Since we have derived a contradiction, it indicates that the system of equations is inconsistent and there are no solutions.
[tex]\[ \text{No solutions} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.